Functional Recovery and Cognitive Improvement in Poststroke Rehabilitation through Integrated Yoga and Naturopathy Intervention - Shweta Mishra; Sriloy Mohanty; Ragini Shrivastava; Monika Pathania (International Journal of Yoga, 2024)
Despite advancements in acute medical management, poststroke rehabilitation (PsR) remains a critical aspect in maximizing recovery and quality of life (QOL) for stroke survivors. In the present case report, poststroke survivor was administered a 90-day tailored integrated yoga and naturopathy (IYN) intervention including daily neutral arm bath, partial massage, and yoga therapy. Following interventions, clinically significant improvement in the range of motion of joints, handgrip strength (Lt. 2.7 kg vs. 14.9 kg), improvement in mid-arm circumference, gait, and cognition (Montreal Cognitive Assessment scores 16 vs. 29) was achieved. In QOL, there was an improvement in each domain of the Short Form 36 questionnaire except for role limitations due to the physical health domain. Improvement in blood pressure (150/60 mmHg vs. 118/70 mmHg) led to a reduction in need of medication. Notably, there was improvement in depression (19 vs. 08), anxiety (18 vs. 08), and stress (21 vs. 07) scores. This case report underscores the potential of IYN intervention in PsR.